Non-epitaxial pulsed laser deposition of Ag2Se thermoelectric thin films for near-room temperature applications. Issue 10 (1st August 2016) - Zhou, Kexiong; Chen, Jikun; Zheng, RenKui; Ke, Xinyou; Zhang, Tiansong; Shi, Xun; Chen, Lidong
Abstract: Non-epitaxial growth of Ag2 Se thermoelectric thin films on (La, Sr) (Al, Ta)O3 or glass substrates at a relatively low temperature of 100 °C has been achieved by using pulsed laser deposition (PLD). The deposition kinetics has been optimized by varying the background interactions with laser induced plasma plume. The shockwave plasma expansion is to be critical for the structure, composition and morphologies of thin films. As-grown Ag2 Se thin films under the optimized deposition condition exhibit comparable transport performances as compared to the reported Ag2 Se bulk materials at similar carrier concentrations. The non-epitaxial correlation between the Ag2 Se thin films and their substrates is expected to benefit for the further fabrication of in plan thermoelectric micro-devices for room temperature applications.